Negotiating Reconciliation in Peacemaking : Quandaries of Relationship Building - Rosoux, Valerie; Anstey, Mark (Springer International Publishing : Imprint: Springer, 2017)
This book offers a unique approach to reconciliation as a matter for negotiation, bringing together two bodies of theory in order to offer insights into resolving conflicts and achieving lasting peace. It argues that reconciliation should not be simply accepted as an 'agreed-upon norm' within peacemaking processes, but should receive serious attention from belligerents and peace-brokers seeking to end violent conflicts through negotiation. The book explores different meanings the term 'reconciliation' might hold for parties in conflict - the end of overt hostilities, a transformation in the quality of relations between warring groups, a vehicle of accountability and punishment of human rights abusers or the means through which they might somehow acquire amnesty, and as a means of atonement and to material reparation. It considers what gives energy to the idea of reconciliation in a conflict situation-why do belligerents become interested in settling their differences and chang ing their attitudes to one another? Using a range of case studies and thematic discussion, chapters in this book seek to tackle these tough questions from a multidisciplinary perspective. Contributions to the book reveal some of the complexities of national and international reconciliation projects, but particularly diverse understandings of reconciliation and how to achieve it. All conflicts reflect unique dynamics, aspirations and power realities. It is precisely because parties in conflict differ in expectations of reconciliation outcomes that its processes should be negotiated. This book is a valuable resource for both scholars and practitioners engaged in resolving conflicts and transforming fragmented relations in conflict and post-conflict situations.
Keywords: Social sciences.; Social policy.; Economic development.; Community psychology.; Environmental psychology.; elektronické knihy; electronic books